Фільтраційне сушіння дрібнодисперсних залізовмісних матеріалів - Симак, Дмитро Михайлович (Національний університет "Львівська політехніка", 2012)
Дисертацію присвячено теоретичним та експериментальним дослідженням гідродинаміки, динаміки і кінетики фільтраційного сушіння дрібнодисперсних залізовмісних матеріалів, які використовують як коректуючі додатки під час виробництва портландцементного клінкеру, зокрема, кек глиноземний, шлам з відвалів Камиш-Бурунського залізорудного комбінату, піритні недогарки. Отримано критеріальні рівняння для опису гідродинаміки фільтраційного сушіння на основі внутрішньої задачі гідродинаміки. На основі експериментальних досліджень отримано критеріальні залежності для визначення коефіцієнтів тепло- й масовіддачі та встановлена аналогія між зовнішнім теплообміном і масообміном. Досліджено зміну температури по висоті шару дрібнодисперсного матеріалу й запропоновано розрахункові залежності для визначення її зміни, встановлено її вплив на інтенсивність фільтраційного сушіння. Запропоновані розрахункові залежності дають змогу прогнозувати енергетичні затрати під час проектних розрахунків нового сушильного обладнання. Розроблено принципову схему сушильної установки, яка враховує кінетичні й фізико-механічні властивості дрібнодисперсних матеріалів. Основні результати передані для впровадження у виробництво цементу та в навчальний процес. The thesis is devoted to study theoretical and experimental research of hydrodynamics, dynamics and kinetics of fine iron materials filtration drying, that are used as a corrective element to the application of clinker in the cement, particularly cake-clay, the pyrit cinders sludge dumps from Kamysh Burunsky-iron plant. It should be noted, that the cement production in Ukraine is spreading and becoming one of the most energy consuming processes. Statistical data is showing, that, the ferrous materials make up to two – tree percents out of the total weight of the charge and are dried in a rotary drying drums with limestone and clay. The humidity in such a drum is much lower, and grain size is to certain extend larger. Because such materials are low disperse they are limiting the speed of heat in a drying drum and the coefficients of heat and mass transfer. Therefore, it is recommended, that these parts should be dried separately by means of filtration method. In order to intensify the process, reduce energy costs and avoid environmental pollution by low disperse materials, the following research was developed by means of hydrodynamic and kinetic filtration drying of ferrous materials. Based on experimental investigations of hydrodynamics agent thermal filtering through the stationary layer of fine material, the coefficient of hydraulic resistance was defined, which enables to predict the energy cost of a pressure differential in the filtration drying design installation. The criteria equations for hydrodynamic stationary layer of fine material on the basis of the internal problems of hydrodynamics, which added geometric simplex that characterizes the exterior problem was made. The thesis studied the kinetics of filtration drying ferrous materials with different process parameters and the layer height. It has been highlighted, that the kinetic curves have a consistent character and intensity of moisture removal in time and are dependent on the drying capacity of the thermal agent. If the growth rate of thermal filtering agent or temperature slope of straight sections increases – it is reflecting the growing intensity of moisture removal. In the case of constant speed filter heat agent intensity of moisture removal is independent of the layer height, as straight plots are parallel. Based on experimental investigations of the process of filtration drying returned criteria dependence for determining the coefficients of heat and mass transfers and established an analogy between external heat exchange and mass transfer. These equations allow to calculate the optimal coefficients of heat and mass transfer and select the necessary parameters of the thermal agent for high-intensity process under the given conditions. In this paper the theoretical aspects of fine materials filtration drying is developed. It was determined, that the filtration process of dispersed material drying consists of three stages. The formation height of the front changes moisture content was identified to determine the average mean temperature of the coolant. The minimum height of the material’s layer on which the thermal agent is fully saturated with moisture at different speeds and filter are tested for adequacy of the proposed model for the filtration drying mechanism. The paper presents the results of equilibrium research of ferrous materials moisture depending on the relative humidity of the thermal agent, calculated coefficients and those are the approximation of dependence, which allows to estimate equilibrium states for dried materials. The dynamics of heat transfer between the stationary layer of dry material and the thermal dispersion agent were considered, in other words the temperature change in layer height of fine material, number of dependences were proposed to determine its change. The effect on the intensity of filtration drying is determined. The number of appropriate dependences were obtained by author, that are based on the analysis and adequacy verification and are followed by the theoretical calculations. It has been highlighted, that the temperature of the thermal agent decreases the height layer and such a process is not isothermal. Based on the synthesis of theoretical and experimental investigations of ydrodynamics, kinetics, dynamics, heat transfer and mass transfer, the schematic diagram was developed of tape drying installation, which takes into account kinetic and physic-mechanical fine materials features and implements the filtration method of drying. Schematic diagram of the dryer is protected by Patent of Ukraine and is following obtained scientific results. The synthesis of theoretical and experimental studies of this method for calculating the basic structural dimensions for the proposed filtration installation of filtration drying depending on the required performance parameters and thermal agent (speed and temperature of thermal filtering agent) were made. Theoretically calculated economic benefit from the introduction of filtration drying in production was performed by author, energy costs of drying process for the three iron materials and comparisons of these indicators with similar indicators, that are typical for the rotating drum were made. The main scientific results of the thesis were submitted and could be used for the development of specification and implementation in production and during the learning process. Диссертацию посвящено теоретическим и экспериментальным исследованиям гидродинамики, динамики и кинетики фильтрационной сушки мелкодисперсных железосодержащих материалов, которые используются как корректирующие добавки при производстве портландцементного клинкера, в частности кек глиноземный, шлам из отвалов Камыш-Бурунского железорудного комбината, пиритные огарки. Получены критериальные уравнения для описания гидродинамики фильтрационной сушки на основе внутренней задачи гидродинамики. На основе экспериментальных исследований получены критериальные зависимости для определения коэффициентов тепло- и массоотдачи и установлена аналогия между внешним теплообменом и массообменом. Исследовано изменение температуры по высоте слоя мелкодисперсного материала и предложены расчетные зависимости для определения ее изменения, установлено ее влияние на интенсивность фильтрационной сушки. Предложенные расчетные зависимости позволяют прогнозировать энергетические затраты при проектных расчетах нового сушильного оборудования. Разработана принципиальная схема сушильной установки, которая учитывает кинетические и физико-механические свойства мелкодисперсных материалов. Основные результаты переданы для внедрения в производство цемента и в учебный процесс.
Filtration drying of fine ferrous materials
Фильтрационная сушка мелкодисперсных железосодержащих материалов
Keywords: кек глиноземний; піритні недогарки; шлам залізорудних комбінатів; гідродинаміка; теплообмін; вологовміст; температура; тепловий агент; масообмін; кінетика; динаміка; фільтраційне сушіння; cake-clay; pyrit cinders; iron ore slurry; hydrodynamics; heat; moisture; temperature; thermal agent; mass transfer; kinetics; dynamics; filtration drying; кек глиноземный; пиритные огарки; шлам железорудных комбинатов; гидродинамика; теплообмен; влагосодержание; температура; тепловой агент; массообмен; кинетика; динамика; фильтрационная сушка